Ulcerative colitis in a multiracial Asian country: racial differences and clinical presentation among Malaysian patients. - Tan, Yan-Mei; Goh, Khean-Lee (2005)
UC is an uncommon disease in Malaysia, but racial differences exist. The Indians had the highest prevalence of UC with the Chinese demonstrating the least extensive disease.